Changing industrial structure to reduce carbon dioxide emissions: a Chinese application - Chang, Ning (Journal of cleaner production, 2015)
Increasing concern about carbon dioxide (CO2) emission reduction demands knowledge about the production structure of an economy. Information on productive linkages yields insight about forward and backward emission effects associated with sectoral inputs and outputs and serves as an essential starting point to identify the optimised industrial structure under the constraint of CO2 emission. This paper proposes a combined linkage analysis and multi-objective programming approach to identify the key CO2 emission sectors and the optimised production structure with respect to emission reduction target. As a demonstration, the proposed approach is applied to data from China in 2007. The result shows that to reduce CO2 emissions from 5707.16 to 5452.12 million tonnes, China needs to change its industrial structure by focussing on industrial groups as defined by linkage characteristics, which would lead to a subsequent GDP decrease of 82.59 billion Yuan. From a policy standpoint, the analytical techniques described in this paper can provide valuable information for planners and decision makers to formulate feasible and practical industrial polices with implications for CO2 emissions. •This paper aims to identify key sectors and the optimised production structure with respect to CO2 emission in an economy.•A linkage analysis combined with multi-objective programming approach is proposed.•Mitigation measures should focus on industrial groups defined by economic and emission linkages.•The proposed approach is applied to data from China in 2007.